The relationship between pistol Olympic shooting performance, handgrip and shoulder abduction strength - Mon-Lopez, D.; Zakynthinaki, M. S.; Cordente, C. A.; Garcia-Gonzalez, J. (Journal of Human Kinetics, 2019)
The ability to stabilize the gun, a crucial factor for performance in air pistol Olympic shooting, is thought to be strongly related to the muscular work of the shooter's shoulder and forearm. The objective of the present study was to confirm this relationship by analysing the influence of maximal finger flexor forces and maximal isometric shoulder force on performance in female air pistol shooting. Twentythree female pistol shooters participated in the study. Handgrip and shoulder force data were recorded under competition conditions, during the official training time of national Spanish championships on the day previous to the competition and at the official training stands. Performance was measured as the total score of 40 shots at competition. Linear regressions between performance and age, weight, height, training experience, body mass index (BMI), mean and maximal finger flexor and shoulder forces were calculated. Significant correlations were found between performance and a) training hours b) peak finger flexor force relative to the BMI, and c) peak isometric force of the shoulder abduction relative to the BMI. The study concludes that there is a statistically significant correlation between performance and muscular forces exerted by the athletes relative to their BMI. Appropriate muscular strength training programs are therefore necessary in female air pistol Olympic shooting. Key words: score, deltoid force, dynamometer, BMI, performance.